Revisiting The Second Wave Impacts of The Look-East Policy in Malaysia - Ismail, Hanim; Khalid, Kartini binti Aboo Talib @; Ramli, Nurul Asmaa (Journal of Ecohumanism, 2025)
The Look East Policy (LEP), initiated by Malaysia in 1982, had two primary goals: to enhance workers' ethics, skills, efficiency, and knowledge by adopting positive values from Japan and Korea, and to improve productivity and quality levels. This article evaluates the impact of the second wave of LEP (LEP 2.0) after 40 years, building on the assumption that LEP 2.0 benefits both Japan and Malaysia, similar to the first wave, which primarily targeted Malaysia's growth. The study aims to assess the success of LEP 2.0's implementation and its empowerment over the past four decades. Data was collected through interviews and focus groups involving 13 stakeholders directly connected to LEP. Using thematic analysis of interview transcripts and the Policy Cycle process, the study found that work ethics, cultural factors, Japanese values, and loyalty to employers were key contributors to improved work quality. However, LEP's success in fully embedding Japanese work culture and values in Malaysia was partial. Nonetheless, LEP 2.0 strengthened Malaysia-Japan cooperation and fostered mutual benefits. Overall, the study highlights both achievements and limitations in realizing LEP’s objectives.